Analisis penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada usaha mikro di Toko C2 Mart5 - Kamalaheng, Afrilia; Mawikere, Lidia M.; Maradesa, Djeni (Manajemen Bisnis dan Keuangan Korporat, 2025)
The Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) were introduced to simplify financial reporting for MSMEs and improve business accountability. This study aims to analyze the application of SAK EMKM in financial reporting practices at C2 Mart, a micro business operating in Minahasa Regency. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation of the store’s accounting practices. The findings reveal that C2 Mart utilizes a digital application to manage transactions and generate financial reports, including the statement of financial position and income statement. However, these reports are not fully aligned with SAK EMKM, particularly regarding asset depreciation, liabilities, and the absence of notes to financial statements. The study highlights the importance of improving accounting literacy among micro-entrepreneurs and enhancing the role of simple digital accounting tools in supporting standardized financial reporting. This research contributes to the discourse on MSME financial management by showing the gap between digital accounting practices and compliance with SAK EMKM, offering insights for regulators, practitioners, and small business owners.